Charm production and fragmentation fractions at midrapidity in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Kroesen, Martin; et al. (Journal of high energy physics, 2023)
Measurements of the production cross sections of prompt D0, D+, D*+, $$ D_{s}^{+} $$, $$ Λ_{c}^{+} $$, and $$ Ξ_{c}^{+} $$charm hadrons at midrapidity in proton-proton collisions at $$ \sqrt{s} $$= 13 TeV with the ALICE detector are presented. The D-meson cross sections as a function of transverse momentum (pT) are provided with improved precision and granularity. The ratios of pT-differential meson production cross sections based on this publication and on measurements at different rapidity and collision energy provide a constraint on gluon parton distribution functions at low values of Bjorken-x (10−5-10−4). The measurements of $$ Λ_{c}^{+} $$($$ Ξ_{c}^{+} $$) baryon production extend the measured pT intervals down to pT = 0(3) GeV/c. These measurements are used to determine the charm-quark fragmentation fractions and the $$ c\overline{c} $$production cross section at midrapidity (|y| < 0.5) based on the sum of the cross sections of the weakly-decaying ground-state charm hadrons D0, D+, $$ D_{s}^{+} $$, $$ Λ_{c}^{+} $$, $$ Ξ_{c}^0 $$and, for the first time, $$ Ξ_{c}^{+} $$, and of the strongly-decaying J/ψ mesons. The first measurements of $$ Ξ_{c}^{+} $$and $$ Σ_{c}^{0,} $$fragmentation fractions at midrapidity are also reported. A significantly larger fraction of charm quarks hadronising to baryons is found compared to e+e− and ep collisions. The $$ c\overline{c} $$production cross section at midrapidity is found to be at the upper bound of state-of-the-art perturbative QCD calculations.
Gesehen am 07.11.2024
The ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1020 weitere Personen]
Im Titel steht der Ausdruck "s" unter dem Wurzelsymbol